2019
DOI: 10.1016/j.euroneuro.2017.08.148
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Telomere Length and Mitochondrial Dna Copy Number in Suicide Completers

Abstract: Short telomere length (TL) occurs in individuals under psychological stress, and with various psychiatric diseases. Recent studies have also reported mitochondrial DNA copy number (mtDNAcn) alterations under several neuropsychiatric conditions. However, no study has examined whether aberrant TL or mtDNAcn occur in completed suicide, one of the most serious outcomes of mental illnesses. TL and mtDNAcn in post-mortem samples from 528 suicide completers without severe physical illness (508 peripheral bloods; 20 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Notably, a postmortem study found that people who had died by suicide had a higher mtDNAcn in peripheral blood but a lower mtDNAcn in the prefrontal cortex compared to controls. 62 Shorter telomere length was also identified in both the peripheral blood and prefrontal cortex of the same people, showing an opposite relationship between telomere length and mtDNAcn in postmortem blood and brain tissue. However, whether these peripheral biomarkers accurately reflect neuronal biomarkers remains unclear, and this is a methodological limitation of human research involving clinical populations.…”
Section: Limitationsmentioning
confidence: 98%
“…Notably, a postmortem study found that people who had died by suicide had a higher mtDNAcn in peripheral blood but a lower mtDNAcn in the prefrontal cortex compared to controls. 62 Shorter telomere length was also identified in both the peripheral blood and prefrontal cortex of the same people, showing an opposite relationship between telomere length and mtDNAcn in postmortem blood and brain tissue. However, whether these peripheral biomarkers accurately reflect neuronal biomarkers remains unclear, and this is a methodological limitation of human research involving clinical populations.…”
Section: Limitationsmentioning
confidence: 98%
“…Therefore, TL largely reflects cellular biological aging (Mather et al, 2011). Similar to DNAm age, TL shortening has been reported in individuals with age-related diseases, including psychiatric disorders, such as MDD (Simon et al, 2006), BD (Rizzo et al, 2013), schizophrenia (Kao et al, 2008), PTSD (O'Donovan et al, 2011), completed suicide (Otsuka et al, 2017), and alcohol dependence (Kang et al, 2017). Recently, Lu and colleagues developed DNAmbased TL (DNAmTL) based on 140 CpG sites from blood samples and showed that DNAmTL of leukocytes is more strongly associated with chronological age than measured leukocyte TL (LTL) and outperforms LTL in predicting mortality and morbidity (Lu et al, 2019b).…”
mentioning
confidence: 94%